2006
DOI: 10.1164/rccm.200601-084oc
|View full text |Cite
|
Sign up to set email alerts
|

DNAH5 Mutations Are a Common Cause of Primary Ciliary Dyskinesia with Outer Dynein Arm Defects

Abstract: Rationale: Primary ciliary dyskinesia (PCD) is characterized by recurrent airway infections and randomization of left-right body asymmetry. To date, autosomal recessive mutations have only been identified in a small number of patients involving DNAI1 and DNAH5, which encode outer dynein arm components. Methods: We screened 109 white PCD families originating from Europe and North America for presence of DNAH5 mutations by haplotype analyses and/or sequencing. Results: Haplotype analyses excluded linkage in 26 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
255
2
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 302 publications
(288 citation statements)
references
References 29 publications
21
255
2
10
Order By: Relevance
“…It is the human orthologue of the Chlamydomonas c-heavy chain gene, the mutants of which are slow-swimming algae with ultrastructural ODA defects [18,33]. Mutations in human DNAH5 are regularly associated with ODA defects, random left-right asymmetry and male infertility [18,34,35]. The mutational prevalence of DNAH5 is currently known in a total of 134 PCD families [18,35].…”
Section: Dnah5mentioning
confidence: 99%
“…It is the human orthologue of the Chlamydomonas c-heavy chain gene, the mutants of which are slow-swimming algae with ultrastructural ODA defects [18,33]. Mutations in human DNAH5 are regularly associated with ODA defects, random left-right asymmetry and male infertility [18,34,35]. The mutational prevalence of DNAH5 is currently known in a total of 134 PCD families [18,35].…”
Section: Dnah5mentioning
confidence: 99%
“…For nNO validation studies at six (non-UNC) sites, PCD was confirmed by PCD-specific ciliary EM defects and, by the presence of biallelic mutations in PCD genes (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Informed consent was obtained at the University of North Carolina at Chapel Hill and collaborating institutions under the auspices of Committees on the Protection of the Rights of Human Subjects.…”
Section: Original Researchmentioning
confidence: 99%
“…The DNAH5 product is a major motor protein of outer dynein arms. Its mutations were observed in more than 25% of PCD patients [98].…”
Section: Primary Ciliary Dyskinesia (Pcd)mentioning
confidence: 99%